SUPRESSION OF MICROSOMAL OXIDATION WEAKENS HISTOCHROME’S DIURETIC EFFECT AT RATS - O. S. Talalaeva; A. Yu. Zharikov; Ya. F. Zverev; S. A. Fedoreyev; V. M. Bryukhanov; V. V. Lampatov (Бюллетень сибирской медицины)
Histochrome is the medicinal form of echinochrome (2, 3, 5, 6, 8-pentahydroxy-7-ethyl-1,4-naphthoquinone). Arisen during clinical application of the drug questions concerning its biotransformation have predetermined the aim of this research: to study participation liver monooxygenase system in maintenance of histochrome’s pharmacological activity.Simple and informative method of the lifetime control of liver monooxygenase systems influence on a metabolism of a medical product is the estimation of changes of pharmacological effect of a r esearched preparation on a background microsomal oxidations i nhibitor. In experiments on rats chloramphenicol action on diuretic effect of histochrome, as the most convenient for screening, was i nvestigated.To control group of animals during 10 days were hypodermically entered by histochrome in a doze of 10 mg/kg (n = 15). Experimental animals preliminary oral received 50 mg/kg of chloramphenicol before three hours of histochrome introduction (n = 16). In both groups of animals measured volume daily excretion of water, creathinin, sodium and potassium ions excretions in experimental rats each two days. The initial level of parameters of excretory kidneys functions were estimated before introduction of preparations at animals.Long-term histochrome’s injection was followed by a fivefold increasing of water excretion and simultaneously creathinin growth one. Allocation of ions of sodium was statistically significantly increased by 11-th day of experiment, and potassium ions – since the ninth day of histochrome injection. In conditions preliminary chloramphenicol applications volume daily daily urine output and creathinin excretion were essentially less control parameters. Allocation with urine of ions of sodium was decreased almost twice in comparison with the values, fixed at introduction histochrome. Excretion potassium ions ware corresponded to an initial level during all period of supervision.Taking into account, that chloramphenicol is powerful inhibitor of microsomal oxidations in a liver, it was logical to assume, that excretion functions decrease of kidneys was connected to oppression of the echinochrome metabolism, and the diuretic effect of a preparation was caused not so much primary substance, how many of its metabolism products. Most likely, echinochrome metabolite raises speed glomerular filtrations, providing diuretic reaction of a preparation.